Smart parking guidance system - Morsin, Marlia (2010)
With the increasing growth of automotive industrial in our world, the demand for the vacant parking is expected to grow rapidly in near future. By using the technology which is available nowadays, intelligent parking system is needed to reduce the problems faced by the vehicle owner. The design of Parking Guidance System using VHDL is used to guide the driver to the vacant space in a short time. With the vacant spaces display on the entrance gate, the driver is able to know is there any vacant space in the building and driver will be guided to the vacant space by the display in the building. After this system is designed, it will be implemented to Altera DE II board by using the Quartus II software. In this Parking Guidance System, it contained counter system, censoring system and display system. The counter system is used to count the total vacant space which is available and counting the total vehicle in the building. Light detector resistor being used in the censoring system to detect either any vacant space was parked by any vehicle and the data will be sending to the main processor in Altera DE II board for process. The display system is used to display all the data which was sent by the processor in the main entrance of the parking building and specified location to guide the driver to the vacant space. A programming system was wrote in VHDL coded and being applied in the system by using the Altera DE II board, the Altera’s Quartus-II being used as the interface between these hardware for downloading purpose. The process of the programming will drive the output to be display in the display components. It will be shown by the seven segment display and the LED display which will able to drive the consumer to the located vacant space.